The Analyze Factor that Related with Joint Pain in Postmenopausal Mothers - Mubarokah Isnaeni; Mira Triharini; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2016)
Introduction : Menopause can be interpreted as a physiological condition of the woman who has entered a period ofaging (aging) which is characterized by decreasing hormonal levels of estrogen. Decreased estrogen can lead toosteoarthritis and osteoartrasis due to decreased estrogen causes decreased collagen matrix so that the cartilagebecomes damaged and cause pain. The incidence of joint pain disease is relatively high, ie 1-2% of the total population inIndonesia is estimated to figure rose steadily increase until 2025 with an indication of more than 25% will experienceparalysis. This study aimed to determine factors associated with joint pain in women in the menopausal Public HealthCenter Randegan Tanggulangin District of Sidoarjo for the prevention of postmenopausal mothers did not experiencesevere joint pain. Method : This research used a Cross Sectional design. The population in the study were allpostmenopausal mothers who come to visit the Poly content with a sample of 20 people. Sampling using purposivesampling. The independent variables were age, BMI, family history, and history of trauma. The dependent variable wasthe incidence of joint pain. Collecting data with interviews, weight scales, height measurement and medical records. Theanalysis used was Spearman's Rho test. Result : The results showed age (p = 0.00), BMI (p = 0.00), history of family (p= 0.00), and a history of trauma (p = 0.021) there is a relationship with the incidence of joint pain. The research provesthat last elderly, obese’s BMI category, history of family, and history of trauma is a factor that can cause joint painin women with postmenopausal dominant factor obese BMI (r = 0.894). Discuss : Expected to society especiallymenopausal mother know about the factors that influence the occurrence of joint pain that IMT, so mother menopausemotivated to maintain their weight by regulating healthy diet and low-fat and regular exercise in accordance with the abilityto increase bone strength and joint flexibility.